Dynamically Crystalizing Liquid‐Crystal Elastomers for an Expandable Endplate‐Conforming Interbody Fusion Cage. Issue 1 (5th December 2019) - Volpe, Ross H.; Mistry, Devesh; Patel, Vikas V.; Patel, Ravi R.; Yakacki, Christopher M.
Abstract: Degenerative disc disease (DDD) is the leading cause of low back pain and radiating leg pain. DDD is commonly treated surgically using spinal fusion techniques, but in many cases failure occurs due to insufficient immobilization of the vertebrae during fusion. The fabrication and demonstration of a 3D‐printed semi‐crystalline liquid crystal elastomer (LCE) spinal fusion cage that addresses these challenges in particular subsidence are described. During implantation of the fusion cage, the LCE is rubbery and capable of deforming around and conforming to delicate anatomy. In the hours following implantation, the device crystallizes into a rigid, structural material with the modulus increasing tenfold from 8 to 80 MPa. In the crystalline regime, a 3D‐printed prototype device is capable of enduring 1 million cycles of physiologic compressive loading with minimal creep‐induced ratcheting. Effects of LCE molecular architecture on the rate and magnitude of modulus increase, material processability, and mechanical properties are explored. This fundamental characterization informs a proof‐of‐concept device—the first bulk 3D printed LCE demonstrated to date. Moreover, the novel deployment strategy represents an exciting new paradigm of spinal fusion cages, which addresses real clinical challenges in expandable interbody fusion cages. Abstract : In this study, direct ink writing of liquid crystal elastomers is used to manufacture a spinal fusion cage prototype capable of time‐dependent crystallization in situ. A systematic study of the structure–property relationships of the material supports future development of the material for orthopedic and load bearing applications.